Plan-Process Factor's Effect on Talent Management and Succession Planning Programs - Kharroub N.; Isa A.A.B.M.; Islam M.K. (World Scientific and Engineering Academy and Society, 2025)
-The aim of the current study is to explore the effect of factors related to the Plan (Mission Clarity and Rewards & Compensation) and the Process (Policy & Procedures and Career Development) on the Talent Management and Succession Planning Programs in Saudi Arabia, in addition, this study will focus on the mediating effect of the Organizational Productivity on the relationship between the variables. To achieve these objectives, this study followed the quantitative research methods through the distribution of 408 questionnaires to the employees of the Saudi Electricity Company. The results showed that Mission Clarity, Rewards & Compensation, Policy & Procedures, and Career Development have a significant relationship with Talent Management and Succession Planning. In addition, Organizational Productivity has a significant mediating effect on the relationship between Mission Clarity, Rewards & Compensation, and Policy & Procedures with Talent Management and Succession Planning. However, Organizational Productivity has insignificant mediating effect on the relationship between Career Development and Talent Management and Succession Planning. ? 2024, World Scientific and Engineering Academy and Society. All rights reserved.